Perkembangan Kurikulum Madrasah 2002-2013: (Studi pada Madrasah Aliyah Mutmainah-Bogor) - Hendi Irawan (Neolectura, 2022)
Curriculum is a tool to achieve educational goals. Hamalik (2017) states that curriculum objectives are goals to be achieved by a study program, field of study, and a subject, which are structured based on institutional objectives. As an important tool for achieving goals, the curriculum must be adaptive to changing times and advances in science and technology. In addition, the curriculum must also develop in accordance with developments in educational theory and practice. The writing of this article is the result of previous research which aims to determine the development of the 2002-2013 madrasah curriculum in its implementation at Madrasah Aliyah Mutmainah-Bogor. The method used in this research is a qualitative method with a descriptive approach, which is a way of collecting data and information as well as existing symptoms according to what they were at the time the research was conducted. The madrasa's efforts to adapt were not easy, even in the adaptation process it resulted in an Educational Dualism between public schools and religious schools. This dualism was inherited from the Dutch colonialists since the colonial period, where the Dutch colonials were indebted to Indonesia which was an ethical policy.